Palladium-Catalyzed Routes to Geranylated or Farnesylated Phenolic Stilbenes: Synthesis of Pawhuskin C and Schweinfurthin J - Singh, Mandeep; Argade, Narshinha P. (Synthesis, 2012)
Starting from double MOM-protected phloroglucinol, the facile total syntheses of bioactive natural products pawhuskin C and schweinfurthin J were accomplished in good overall yields. The Heck, Stille, or Suzuki coupling reactions of two different electron-rich phenolic segments bearing geranylated or farnesylated units were involved in the decisive step. The Sonogashira coupling reaction followed by palladium-catalyzed chemo- and stereoselective cis-reduction of an alkyne unit and subsequent isomerization to give the desired natural products is also described.
Keywords: total synthesis; natural products; geranylated or farnesylated stilbenes; palladium-catalyzed coupling reactions; phloroglucinol